INPATIENT CARE UTILIZATION AMONG ELDERLY IN INDONESIA: A CROSS-SECTIONAL STUDY FROM INDONESIA FAMILY LIFE SURVEY - Haerawati Idris; Nurafni (The Indonesian Journal of Public Health, 2023)
Introduction: The increasing number of the elderly is worrying. It is a concern in public health issues. The elderly have higher susceptibility to chronic diseases. Aims: To identify the factors affecting inpatient care utilization among the elderly population in Indonesia. Methods: Data from the 2014 Indonesian Family Life Survey were used, representing 83% of the Indonesian population. Additionally, Andersen’s theory of healthcare service utilization model was applied. This study applied a cross-sectional design. The sample consisted of 5,325 respondents 60 years in age or older. The chi-square test and multivariate analysis using a multiple logistic regression test were used to analyze the data. Result: This study found 222 of its respondents utilized inpatient care (4.2%). The characteristics that had a significant correlation with the utilization of inpatient care were women, middle-school education, high education, Sumatera region, urban area, health insurance ownership, low economy status, middle economy status, high economy status, very high economy status, sick perception, smoking habit and obesity. Conclusion: The most dominant predictor was the high economy status. The health-insured elderly are able to receive inpatient care without bearing the financial burden. The government should provide health insurance for the elderly in Indonesia.